Hak-hak Anak Zina Perspektif Fiqh Empat Madzhab - Muhammad Ihwan (Program Pascasarjana Universitas Ibrahimy, 2017)
Islam was very attentive to the child rights, regardless of who their parents. A child has the lineage right, to get their inheritance right, to get living right, to get equal treatment right, etc. However, this has not been fully achieved. One of them happens to children born out of wedlock, or better known as the bastard. They were treated unilaterally from the society, society looks bastard is a disgrace. As if that bastard follow their parent’s behavioral depravity. This study contains the views of the jurists of four mazhab associated with bastard. There are three issues discussed in this article involve problem of bastard be the imam of shalat, mu'adzin, and witness. This study aimed to find out the views of the jurists about bastard. The method used in this research is qualitative method, which describe the views of the jurists of four mazhab thought about natural child. Of the three problems associated with natural child, jurists of four mazhab have different opinions.